Germinação e armazenamento de sementes de Stylosanthes Sw. em diferentes ambientes - Américo, Fabiana Karla de Araújo (2015)
The forage species of Stylosanthes and its adaptation to different environments have increased demand on the seed trade, which requires accurate information for your use. For the study of seeds conservation is necessary prior knowledge of physiological characteristics and their environmental requirements. The goal this work were establish appropriate conditions of temperature and substrate in germination tests and evaluate the germination of seeds of S. capitata, S. scabra and S. viscosa subjected to different times and storage environments to conservation. The tests were performed in the laboratory of Germination at Universidade Estadual de Feira de Santana-UEFS, Feira de Santana-BA. The temperature tested were: 25, 30 and 20-30 °C and the substrates were on paper (P), roll paper (RP) and commercial Biomix. To evaluate the behavior in conservation, Stylosanthes seeds were stored for 12 months at room temperature (lab), refrigerator, in freezer and in liquid nitrogen. The species S. capitata, S. scabra and S. viscosa showed variability regarding germination. The seeds germination of S. capitata was improved at on paper and temperatures 30 °C constant and 20-30 °C alternating. For S. scabra and S. viscosa seeds were recommended the roll paper at room temperature (25 °C). Seeds of Stylosanthes respond differently to the conditions of storage and germination tests. S. capitata seeds seem to be more tolerant of the storage conditions, remaining vigorous for 12 months. Besides the physical dormancy, seeds of the S. scabra e S. viscosa it seems put forward the physiological dormancy and the maintenance of seeds in controlled laboratory conditions increased the ability of germination, but with reduced vigor.